Femoral Morphology in the Dysplastic Hip: Three‐dimensional Characterizations With CT. Issue 4 (April 2017) - Wells, Joel; Nepple, Jeffrey J.; Crook, Karla; Ross, James R.; Bedi, Asheesh; Schoenecker, Perry; Clohisy, John C.
Abstract: Background: Hip dysplasia represents a spectrum of complex deformities on both sides of the joint. Although many studies have described the acetabular side of the deformity, to our knowledge, little is known about the three‐dimensional (3‐D) head and neck offset differences of the femora of dysplastic hips. A thorough knowledge of proximal femoral anatomy is important to prevent potential impingement and improve results after acetabular reorientation. Questions/purposes: (1) Are there common proximal femoral characteristics in patients with symptomatic hip dysplasia undergoing periacetabular osteotomy (PAO)? (2) Where is the location of maximal femoral head and neck offset deformity in hip dysplasia? (3) Do certain subgroups of dysplastic hips more commonly have cam‐type femoral morphology? (4) Is there a relationship between hip ROM as well as impingement testing and 3‐D head and neck offset deformity? Methods: Using our hip preservation database, 153 hips (148 patients) underwent PAO from October 2013 to July 2015. We identified 103 hips in 100 patients with acetabular dysplasia (lateral center‐edge angle [LCEA] < 20°) and who had a Tönnis grade of 0 or 1. Eighty‐six patients (86%) underwent preoperative low‐dose pelvic CT scans at our institution as part of the preoperative planning for PAO. It is currently our standard to obtain preoperative low‐dose pelvic CT scans (0.75‐1.25 mSv, equivalent to three to five AP pelvis radiographs) on all patients before they undergo PAO unless a prior CT scan is performed at an outside institution. Hips with a history of a neuromuscular disorder, prior trauma, prior surgery, radiographic evidence of joint degeneration, ischemic necrosis, or Perthes‐like deformities were excluded. Fifty hips in 50 patients met inclusion criteria and had CT scans available for review. Hips were analyzed with Dyonics Plan software and characterized with regard to version, neck‐shaft angle, femoral head diameter, head and neck offset, femoral neck length, femoral offset, head center height, trochanteric height, and alpha angle. The maximum head and neck offset deformity was assessed using an entire clockface and an alpha angle ≥ 55° defined coexisting cam morphology. Subgroups included severity of lateral dysplasia: mild (LCEA 15°‐20°) and moderate/severe (LCEA < 15°). Femoral version subgroups were defined as normal (5°‐20°), decreased (≤ 5°), or increased (> 20°). The senior author (JCC) performed all physical examination testing. Results: The mean LCEA was 14° (±4°), whereas the mean femoral anteversion was 19° (±12°). Eight hips (16%) demonstrated relative femoral retroversion (≤ 5°), whereas 26 (52%) showed excessive femoral anteversion (> 20°). Four hips (8%) had ≥ 35° of femoral anteversion. The mean neck‐shaft angle was 136° (±5°). The mean maximum alpha location was 2:00 o'clock (±45 minutes) and the mean maximum alpha angle was 52° (±6°). Minimum head‐neck offset ratio was located at 1:30 with a mean of 0.14 (±0.03). An anterior head‐neck offset ratio of ≤ 0.17 or an alpha angle ≥ 55° was found in 43 (86%) of hips. Twenty‐one dysplastic hips (42%) had an alpha angle ≥ 55°. Mildly dysplastic hips had decreased femoral head and neck offset (9 ± 1) and head and neck offset ratio (0.20 ± 0.03) at 12 o'clock compared with moderate/severe dysplastic hips (10 ± 1 and 0.22 ± 0.03, respectively; p = 0.04 and p = 0.01). With the numbers available, we found that hips with excessive femoral anteversion (> 20°) had no difference in the alpha angle at 3 o'clock (42 ± 7) compared with hips with relative femoral retroversion (≤ 5°; 48 ± 4; p = 0.06). No other differences in femoral morphology were found between hips with mild or moderate/severe dysplasia or in the femoral version subgroups with the numbers available. Anterior impingement test was positive in 76% of hips with an alpha angle ≥ 55° and 83% of the hips with an alpha angle ≤ 55°. No correlation was found between proximal femoral morphology and preoperative ROM. Conclusions: In this subset of dysplastic hips, cam deformity of the femoral head and neck was present in 42% of hips with maximal head‐neck deformity at 2 o'clock, and 82% had reduced head‐neck offset at the 1:30 point. We conclude that cam‐type deformities and decreased head‐neck offset in developmental dysplasia of the hip are common. Patients should be closely assessed for need of a head and neck osteochondroplasty, especially after acetabular correction. Future prospective studies should evaluate the influence of proximal femoral anatomy on surgical results of PAO for dysplastic hips. Level of Evidence: Level IV, prognostic study.